1999
DOI: 10.1074/jbc.274.40.28106
|View full text |Cite
|
Sign up to set email alerts
|

Neuronal Excitation-driven and AP-1-dependent Activation of Tissue Inhibitor of Metalloproteinases-1 Gene Expression in Rodent Hippocampus

Abstract: Understanding of biological function of AP-1 transcription factor in central nervous system may greatly benefit from identifying its target genes. In this study, we present several lines of evidence implying AP-1 in regulating expression of tissue inhibitor of metalloproteinases-1 (timp-1) gene in rodent hippocampus in response to increased neuronal excitation. Such a notion is supported by the findings that timp-1 mRNA accumulation occurs in the rat hippocampus after either kainate-or pentylenetetrazole-evoke… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
43
0
1

Year Published

2001
2001
2009
2009

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 67 publications
(49 citation statements)
references
References 38 publications
5
43
0
1
Order By: Relevance
“…Thus, the increased expression of MMP-2 and MMP-9, especially in the hippocampus, can be attributed to upregulation of IL-6 and TNF-␣, which have been described as the main actors in MMP modulation (19,26,54). TIMP-1 upregulation in the cortex, hippocampus, and hypothalamus could be due to synergistic activation of AP-1 (30) and polyoma enhancer activator 3 sites in the TIMP-1 promoter. TIMP-1 upregulation may be mediated by TNF-␣, levels of which were increased in the same structures as TIMP-1, acting by stimulation of early gene production (38), or may reflect activation of the IL-6-oncostatin M-responsive element located in the TIMP-1 promoter (9).…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the increased expression of MMP-2 and MMP-9, especially in the hippocampus, can be attributed to upregulation of IL-6 and TNF-␣, which have been described as the main actors in MMP modulation (19,26,54). TIMP-1 upregulation in the cortex, hippocampus, and hypothalamus could be due to synergistic activation of AP-1 (30) and polyoma enhancer activator 3 sites in the TIMP-1 promoter. TIMP-1 upregulation may be mediated by TNF-␣, levels of which were increased in the same structures as TIMP-1, acting by stimulation of early gene production (38), or may reflect activation of the IL-6-oncostatin M-responsive element located in the TIMP-1 promoter (9).…”
Section: Discussionmentioning
confidence: 99%
“…One possibility is that rapid conversion of pro-to active-MMP-9 is mediated via tissue plasminogen activator (tPA), a serine protease upregulated during, and required for, L-LTP (Qian et al, 1993;Huang et al, 1996;Baranes et al, 1998), because several tPA-dependent pathways have been shown to affect MMP-9 levels and/or activity in non-neuronal cell types (Cuzner and Opdenakker, 1999;Wang et al, 2003b). The mechanism by which L-LTP-induced levels of active MMP-9 are returned to prestimulation levels is unclear, although activity-dependent regulation of endogenous TIMPs is possible (Rivera et al, 1997;Jaworski et al, 1999). more acute role for MMP-9 in LTP.…”
Section: Rapid Upregulation Of Mmp-9 With L-ltpmentioning
confidence: 99%
“…As a matter of fact, coordination of neuronal plasticity has not only been suggested as IEGs' function, but in a few cases has al-ready been proven (consider, e.g., a pathway of extracellular matrix remodeling driven by AP-1; Refs. 197,209,338). Another important consequence of studies on IEGs/ transcription factors is nuclear localization of the IEGs' protein products that greatly facilitates their immunostaining-based detection, because of excellent spatial resolution and rather simple way of numerical evaluation.…”
Section: Gene Activity As a Mapping Tool: Theoretical And Technicmentioning
confidence: 99%